Model reduction of continuous-time interval systems using eigen spectrum analysis - Singh C.N.; Kumar D.; Samuel P.; Sachan A. (My University, 2025)
This paper presents mixed methods based on Eigen spectrum approach for order reduction of higher-order linear time-invariant continuous-time interval systems. The proposed methods are developed as a combination of Eigen spectrum approach along with the moment matching and differentiation methods by employing Kharitonov's theorem. The system stiffness and pole centroid of higher-order interval systems are preserved in the reduced-order interval models. Therefore, the stability of resulting reduced-order interval model is ensured for a stable higher-order interval system. A comparative analysis of the proposed approaches with well-known existing approaches is included to demonstrate the efficacy of the proposed methods. © 2018 IEEE.